Identifikasi Senyawa Metabolit Kopi Robusta (Coffea canephora) dan Kandungan Kafein Kopi Robusta Akibat Fermentasi Bakteri Asam Laktat Lactobacillus plantarum Menggunakan UPLC-QTOF-MS/MS - Dimas Andrianto; Dimas Andrianto; R. Haryo Bimo Setiarto (Postgraduate, University of Mataram, 2025)
Robusta coffee (Coffea canephora) is one type of plant that has long existed in Indonesia and has high economic value. Robusta coffee beans have the potential to be developed to reduce caffeine levels by treating them with lactic acid bacteria. This study aims to determine the metabolite profile of Robusta coffee from several samples treated with Lactobacilus plantarum bacteria. Samples were taken from the West Java location at the Patani Coffee Plantation. Sample extraction was carried out using the Ultrasonic Assisted Extraction (UAE) method with 96% ethanol. Metabolite content analysis was carried out using UPLC-QTOF-MS/MS with a C18 stationary phase column (Okta Decyl Silica), a mixture of formic acid/water 0.1/99.9 (v/v) and formic acid/acetonitrile 0.1/99.9 (v/v) mobile phases. The results of the analysis were interpreted using Masslynx software. The results showed that the caffeine content in coffee not fermented with Lactobacillus plantarum was 2.40%, coffee fermented with L. plantarum bacteria for 6 hours had an abundance% of 1.76%, and coffee fermented with L. plantarum bacteria for 24 hours had an abundance% of 2.38%. LC-MS/MS analysis identified compounds 35,26, and 25 in three Robusta coffee samples. These results were not significantly different from the fermentation of Lactobacillus plantarum in Robusta coffee beans